High-resolution two-dimensional atomic microscopy in a tripod-type four-level atomic medium via standing wave fields. (30th October 2020) - Idrees, Muhammad; Ullah, Muhib; Amin Bacha, Bakth; Ullah, Arif; Wang, Li-Gang
Abstract: We present an efficient two-dimensional atomic localization in a tripod-type four-level atomic medium using standing-wave fields. The localization behavior is significantly improved, and the maximum localization probability can be achieved under suitable conditions within the one-wavelength domain. Multiple sharp localized peaks are observed in the one-wavelength domain through examination of the absorption of the weak probe field, and theoretically, high-resolution and high-precision atomic localization can be achieved within a region smaller than λ /12 × λ /12, via the exploitation of quantum-coherence effects in laser–matter interactions. The spatial resolution of the atomic localization is extensively improved, compared to the cases with or without microwave fields studied previously. We believe that the results revealed here might have potential applications for atomic nanolithography, neutral-atom laser cooling and trapping, Bose–Einstein condensation and the center-of-mass wave-function measurements.